Neonicotinoids disrupt aquatic food webs and decrease fishery yields - Yamamuro, Masumi; Komuro, Takashi; Kamiya, Hiroshi; Kato, Toshikuni; Hasegawa, Hitomi; Kameda, Yutaka (Science (American Association for the Advancement of Science), 2019)
Invertebrate declines are widespread in terrestrial ecosystems, and pesticide use is often cited as a causal factor. Here, we report that aquatic systems are threatened by the high toxicity and persistence of neonicotinoid insecticides. These effects cascade to higher trophic levels by altering food web structure and dynamics, affecting higher-level consumers. Using data on zooplankton, water quality, and annual fishery yields of eel and smelt, we show that neonicotinoid application to watersheds since 1993 coincided with an 83% decrease in average zooplankton biomass in spring, causing the smelt harvest to collapse from 240 to 22 tons in Lake Shinji, Shimane Prefecture, Japan. This disruption likely also occurs elsewhere, as neonicotinoids are currently the most widely used class of insecticides globally.